The Economic Effects of Involuntary Uniformity in the Financial Reporting of R&D Expenditures - Horwitz, Bertrand N.; Kolodny, Richard (Journal of Accounting Research, 1980)
Bertrand N. Horwitz, Richard Kolodny, The Economic Effects of Involuntary Uniformity in the Financial Reporting of R&D Expenditures, Journal of Accounting Research, Vol. 18, Studies on Economic Consequences of Financial and Managerial Accounting: Effects on Corporate Incentives and Decisions (1980), pp. 38-74